1998
DOI: 10.1038/sj.sc.3100509
|View full text |Cite
|
Sign up to set email alerts
|

Clean intermittent catheterization and prevention of renal disease in spinal cord injury patients

Abstract: Upper urinary tract complications have been reported in about 20 ± 30% of spinal cord injury patients. Their pathogenesis is linked to the presence of high-pressure uninhibited detrusor contractions, high leak point pressure and low bladder compliance. The aim of this study was to evaluate the incidence of upper urinary tract complications in two homogeneous groups of spinal cord injury patients with di erent bladder emptying modalities (intermittent catheterization vs. tapping, abdominal straining, Crede's ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 21 publications
2
33
0
3
Order By: Relevance
“…Bladder-emptying method agreement with recommendations from studies 8,9 that have shown CIC to be a successful long-term option to bladder emptying in SCI individuals. The increased use of CIC was predominant in males.…”
Section: Discussionsupporting
confidence: 57%
“…Bladder-emptying method agreement with recommendations from studies 8,9 that have shown CIC to be a successful long-term option to bladder emptying in SCI individuals. The increased use of CIC was predominant in males.…”
Section: Discussionsupporting
confidence: 57%
“…Furthermore, it has been reported that upper urinary tract complications, for example, urinary tract dilatation and vesicoureteral reflux, are more common in SCI patients with reflex voiding than those with IC. 21 With regard to the etiology, the pathogenesis of these complica- tions is linked to high-pressure uninhibited detrusor contractions, high leak point pressure and low bladder compliance. 21 The presence of urinary tract dilatation and vesicoureteral reflux is not only likely to cause infection but also induces AD in patients with SCI at or above the T6 level.…”
Section: Discussionmentioning
confidence: 99%
“…21 With regard to the etiology, the pathogenesis of these complica- tions is linked to high-pressure uninhibited detrusor contractions, high leak point pressure and low bladder compliance. 21 The presence of urinary tract dilatation and vesicoureteral reflux is not only likely to cause infection but also induces AD in patients with SCI at or above the T6 level. This background might explain our finding of the highest incidence of symptomatic AD in patients with reflex voiding despite the fact that the percentage of AIS A in these patients was not higher than those of IC and indwelling supra-pubic and urethral catheterization.…”
Section: Discussionmentioning
confidence: 99%
“…In 1998, Lim et al 4 reported that only 2 (6.7%) of 30 patients with SCI maintained the same IC method for a year after leaving the hospital. Because the appropriate voiding volume for the IC method is 400-450 ml at a time, a patient with an SCI must maintain a timely fluid intake of 1800-2000 ml per day and must perform catheterization every 4-6 h. 5,6 With such a time-dependent regimen, physiological changes in urinary excretion related to fluid intake or environmental changes may lead to unnecessary catheterizations and early emptying attempts or to overdistension of the bladder. 7,8 These difficulties are universally applicable to spontaneous and passive voiding by straining for maintenance of acceptable detrusor pressures and bladder volumes.…”
Section: Introductionmentioning
confidence: 99%